(untitled) (Proceedings of Southern Federal University. Philology, 2019)
Marianna A. Dudareva (Moscow, Russian Federation) The article deals with the under examined problem in literary studies: a folklore tradition in O. Mandelstam’s poetry. The researchers studied manifestation of mythological tradition in the poet’s artistic world and revealed different archetypal models but they paid no attention to folklore elements. The folklore commentary of one of the poems makes it possible to understand an image structure of the text in the other way and brings a reader to the ontological level of the content. Key words: folklore, literature, Mandelstam, “ideal topos”, Mayakovsky, image of fish. DOI 10.23683/1995-0640-2019-2-98-105